(untitled) (Research, Society and Development, 2020)
Physical activity is associated with a 20% to 30% lower risk of mortality from all causes and the incidence of multiple chronic conditions, including the worsening of orthoarticular problems in people with reduced mobility resulting from a disabling neurological injury. In this context, the present study aims to describe the experience of home care for people with paraparesis due to traumatic brain injury, as a preventive strategy for osteomioarticular complications. This is a descriptive, observational, quantitative study, type of experience based on passive and systematic exercises, supported by Roy & Andrews`s Adaptation Model, with the person with functional dependence and severe spasticity, from 1997 to 2019. Activities they were prescribed and periodically evaluated by the teams of the institutional rehabilitation program, to which the client has had a therapeutic relationship for 22 years, with resources from assistive technology that ensured postural alignment for body safety in the exercises. The experience contributes to the consolidation of rehabilitation nursing interventions with clients with spastic paraparesis, as a long-term daily care procedure aimed at promoting their physical, mental and spiritual integrality.